Host-Adaptive Signatures of H3N2 Influenza Virus in Canine - Li, Xueyun; Liu, Jia; Qiu, Zengzhao; Liao, Qijun; Peng, Yani; Chen, Yongkun; Shu, Yuelong (Frontiers in Veterinary Science, 2021)
Wild aquatic birds are the primary natural reservoir of influenza A viruses (IAVs), although a small number of viruses can spill over to mammals and circulate. The focus of IAV infection in mammals was largely limited to humans and swine variants, until the emergence of H3N2 canine influenza viruses (CIVs), which provides new perspective for interspecies transmission of the virus. In this study, we captured 54 canine-adaptive signatures in H3N2 CIVs through entropy computation, which were largely concentrated in the interaction region of polymerase proteins on ribonucleoprotein (RNP) complex. The receiver operating characteristic (ROC) curves of these sites showed >95% accuracy in distinguishing between the hosts. Eight of the 54 canine-adaptive signatures were shared in avian-human/equine or equine-canine (PB2-82;PB1-361;PA-277;HA-81,172,196,222,489), suggesting their involvement in canine adaptation. Furthermore, we found that IAVs can establish persistent transmission in lower mammals with greater ease compared to higher mammals and 24 common adaptation signatures of H3 IAVs were observed in diverse avian-mammals comparison. There were few human-like residues in H3N2 CIVs, which suggested a low risk of human infection. Our study highlights the necessity of identifying and monitoring the emerging adaptive mutations in companion animals by enhanced surveillance, and provides a basis for mammal adaptation of avian influenza viruses (AIVs).